The Varied Roles of Nuclear Argonaute-Small RNA Complexes and Avenues for Therapy - Jason P Ross; Zena Kassir (Elsevier, 2014)
Argonautes are highly conserved proteins found in almost all eukaryotes and some bacteria and archaea. In humans, there are eight argonaute proteins evenly distributed across two clades, the Ago clade (AGO1-4) and the Piwi clade (PIWIL1-4). The function of Ago proteins is best characterized by their role in RNA interference (RNAi) and cytoplasmic post-transcriptional gene silencing (PTGS) - which involves the loading of siRNA or miRNA into argonaute to direct silencing of genes at the posttranscriptional or translational level. However, nuclear-localized, as opposed to cytoplasmic, argonaute-small RNA complexes may also orchestrate the mechanistically very different process of transcriptional gene silencing, which results in prevention of transcription from a gene locus by the formation of silent chromatin domains. More recently, the role of argonaute in other aspects of epigenetic regulation of chromatin, alternative splicing and DNA repair is emerging. This review focuses on the activity of nuclear-localized short RNA-argonaute complexes in a mammalian setting and discusses recent in vivo studies employing nuclear-directed sRNA for therapeutic interventions. These studies heed the potential development of RNA-based drugs which induce epigenetic changes in the cell.